The effects of a simple optical clearing protocol on the mechanics of collagenous soft tissue. (9th June 2021) - Meador, William D.; Zhou, Jennifer; Malinowski, Marcin; Jazwiec, Tomasz; Calve, Sarah; Timek, Tomasz A.; Rausch, Manuel K.
Abstract: Optical clearing of biological tissues improves imaging depth for light transmission imaging modalities such as two-photon microscopy. In studies that investigate the interplay between microstructure and tissue-level mechanics, mechanical testing of cleared tissue may be useful. However, the effects of optical clearing on soft tissue mechanics have not been investigated. Thus, we set out to quantify the effects of a simple and effective optical clearing protocol on the mechanics of soft collagenous tissues using ovine mitral valve anterior leaflets as a model system. First, we demonstrate the effectiveness of an isotonic glycerol-DMSO optical clearing protocol in two-photon microscopy. Second, we evaluate the mechanical effects of optical clearing on leaflets under equibiaxial tension in a dependent study design. Lastly, we quantify the shrinkage strain while traction-free and the contractile forces while constrained during clearing. We found the optical clearing protocol to improve two-photon imaging depth from 100 μm to 500–800 μm, enabling full-thickness visualization of second-harmonic generation, autofluorescent, and fluorophore-tagged structures. Under equibiaxial tension, cleared tissues exhibited reduced circumferential (p < 0.001) and radial (p = 0.009) transition stretches (i.e. stretch where collagen is recruited), and reduced radial stiffness (p = 0.031). Finally, during clearing we observed 10–15% circumferential and radial compressive strains, and when constrained, 2 mN of circumferential and radial traction forces. In summary, we suggest the use of this optical clearing agent with mechanical testing be done with care, as it appears to alter the tissue's stress-free configuration and stiffness, likely due to tissue dehydration.